Teachers' Perceptions and Readiness for AI-Based Virtual Assistants in Supporting Schools' Learning Transformation - Sibarani, Debora Pratiwi; Cendana, Wiputra; Anggraeni, C. Kiky Puspita (Journal of Practice Learning and Educational Development, 2025)
The rapid development of Artificial Intelligence (AI) brings great potential to the education world holistically, not only changing the way of teaching and learning but also impacting the education system. However, the use of AI in learning is still relatively new and initiatives to introduce AI in schools have not been widely implemented in Indonesia. In fact, it is crucial for teachers to become proficient in using this technology to maximize its benefits for both teachers and students in preparing for future challenges. The purpose of this study is to explore teachers' perceptions toward the use of AI-based virtual assistants in supporting tasks at school and to examine and analyze the teachers’ level of readiness and schools in facing the era of artificial intelligence. This descriptive study was conducted using a hybrid approach, namely a combination of both quantitative and qualitative. Initial data collection involved distributing a Likert-scale questionnaire to 30 teacher respondents from a senior high school that employs national standard curriculum combined with international assessments to value teachers' perceptions of AI use. Subsequently, in-depth interviews were conducted with three participants, including administrators and professional. Data analysis of the questionnaire demonstrated the validity and reliability of the perception instrument used. Furthermore, the interview results clarified the preparations that have been made, will be made, and have not yet been addressed by schools in maximizing the use of AI. This study concludes with recommendations that align with the needs of teachers to acquire these essential skills which can be supported by schools.